The determination of the volume of bank deposits: England 1955-56 - SAYERS, R.S. (PSL Quarterly Review, 2014)
The article considers the present behaviour of the English banking system, essentially reaffirming the validity of the principle that the volume of bank deposits is, in the last resort, determined by the monetary authorities. The author seeks, however, to show how the mechanism has varied in response to recent changes of a technical character. To this purpose, he author examines in detail the influence of the English financial institutions as they currently operate, and clears up how the cash-ratio has lost the guiding function it exercised. JEL: E51, E58, G21